Effect of Organic Carbon and Nitrogen on the Interactions of Morchella spp. and Bacteria Dispersing on Their Mycelium - Lohberger, Andrea; Spangenberg, Jorge E.; Ventura, Yolanda; Bindschedler, Saskia; Verrecchia, Eric P.; Bshary, Redouan; Junier, Pilar (Frontiers in Microbiology, 2019)
In this study we investigated how the source of organic carbon (Corg) and nitrogen (Norg) affects the interactions between fungi of the genus Morchella and bacteria dispersing along their hyphae (fungal highways; FH). We demonstrated that bacteria using FH increase the hydrolysis of an organic nitrogen source that only the fungus can degrade. Using purified fungal exudates, we found that this increased hydrolysis was due to bacteria enhancing the activity of proteolytic enzymes produced by the fungus. The same effect was shown for various fungal and bacterial strains. The effect of this enhanced proteolytic activity on bacterial and fungal biomass production varied accordingly to the source of Corg and Norg provided. An increase in biomass for both partners five days post-inoculation was only attained with a Norg source that the bacterium could not degrade and when additional Corg was present in the medium. In contrast, all other combinations yielded a decrease on biomass production in the co-cultures compared to individual growth. The coupled cycling of Corg and Norg is rarely considered when investigating the role of microbial activity on soil functioning. Our results show that cycling of these two elements can be related through cross-chemical reactions in independent, albeit interacting microbes. In this way, the composition of organic material could greatly alter nutrient turnover due to its effect on the outcome of interactions between fungi and bacteria that disperse on their mycelia.